Effects of Septin-14 Gene Deletion on Adult Cognitive/Emotional Behavior - Chen, Kuan-Ru; Wang, Han-Yu; Liao, Yi-Han; Sun, Li-Han; Huang, Yu-Han; Yu, Lung; Kuo, Pao-Lin (Frontiers in Molecular Neuroscience, 2022)
While various septin GTPases have been reported for their physiological functions, their roles in orchestrating complex cognitive/emotional functions in adult mammals remained scarcely explored. A comprehensive behavioral test battery was administered to two sexes of 12-week-old Septin-14 (SEPT14) knockout (KO) and wild-type (WT) mice. The sexually dimorphic effects of brain SEPT14 KO on inhibitory avoidance (IA) and hippocampal mGluR5 expression were noticed with greater IA latency and elevated mGluR5 level exclusively in male KO mice. Moreover, SEPT14 KO appeared to be associated with stress-provoked anxiety increase in a stress-related navigation task regardless of animals’ sexes. While male and female WT mice demonstrated comparable cell proliferation in the dorsal and ventral hippocampal dentate gyrus (DG), both sexes of SEPT14 KO mice had increased cell proliferation in the ventral DG. Finally, male and female SEPT14 KO mice displayed dampened observational fear conditioning magnitude and learning-provoked corticosterone secretion as compared to their same-sex WT mice. These results, taken together, prompt us to conclude that male, but not female, mice lacking the Septin-14 gene may exhibit increased aversive emotion-related learning and dorsal/ventral hippocampal mGluR5 expressions. Moreover, deletion of SEPT14 may be associated with elevated ventral hippocampal DG cell proliferation and stress-provoked anxiety-like behavior, while dampening vicarious fear conditioning magnitudes.